Smart Box Receiver of IoT-Based Expedition Package Using a QR Code Scan - Ardelia, Alda; Anshori, Moh. Abdullah; Koesmarijanto, Koesmarijanto (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2024)
The increase in internet users makes the purchase of goods online also increase. Someone needs a fast and safe delivery of goods to ensure the goods they buy, but the problem is that couriers often deliver packages when the recipient is not at home, even some couriers are found throwing packages into the fence of the house which can trigger package damage. can accommodate packets to be received. The solution is to make a smart box that is connected to the internet or wifi. how it works is by registering the receipt number that has been obtained from shopping online into the web server. The receipt number will be inputted by the courier to the website via a scan of the QR code, if the receipt is registered, the courier can open the box. Testing the receipt number input by the courier, the results are 100% successful because all receipt numbers have been registered on the web server so that it produces output in the form of an automatic solenoid doorlock opening, and a servo motor rotating 90 degrees pushing the box door open. The results of the response time testing starting from the courier scanning the QR Code and inputting the receipt number into the website until the smart box door opens and locks again after the courier puts the package into the box, the average time is 59.47 seconds